Legal Transendence Theory: Traces and Efforts to Build Transendent Legal Paradigm - I Istani; Wardah Yuspin (Proceeding International Conference Restructuring and Transforming Law, 2022)
Commitment to tackle corruption in a firm, consistent, and integrated manner is an important step to be able to produce law enforcement, provide legal certainty, and benefit the community. This writing aims to describe the comparison of the prevention of corruption by the Government of Uganda and the Government of Indonesia. This type of research is a juridical research with a qualitative doctrinal approach. The results of the study show that there are differences in the prevention of corruption by the Ugandan and Indonesian governments. Corruption countermeasures regulated by the Ugandan government regulations include the cancellation of contracts, monetary fines, bans and imprisonment of perpetrators of corruption. Indonesia